Preparation and Characterization of Activated Carbon from Date Fronds Biomass by Chemical Activation - Ahmad, Ashfaq; M. Al-Swaidan, Hassan; H. Alghamdi, Ahmad (Asian Journal of Chemistry, 2014)
Date’s frond wastes have been used to prepare activated carbons. Methods of production and types of waste materials have an effect on the properties of activated carbons. Date’s tree frond waste is a biomass and used as a precursor to prepare activated carbon by chemical activation with KOH is reported in this work. The characterization of carbon materials is performed by Fourier transform infrared spectroscopy, scanning electron microscopy and nitrogen adsorption. The char was obtained from date fronds at 400 ºC temperature which corresponds to thermogravimetry analysis. A high surface area porous activated carbons was prepared by soaking the date’s frond in KOH solutions. A variety of KOH concentrations such as 0, 5, 10 and 15 % are used. The 15 % concentration of KOH was found the best with the highest surface area 250.25 m2 g-1. The FTIR analysis indicates several functional groups changes on the surface of the activated carbons which are formed during different preparation phases. JSM-scanning electron microscopy of activated carbons indicates cavities and pores on the surface. The maximum BET surface area 250.25 m2 g-1 was found for 15 % KOH activated carbons compared to raw date fronds 4.6 m2 g-1.